Mejora de la competitividad a través de la innovación tecnológica en las micro y pequeña empresas del sector calzado en Trujillo - Castañeda Meléndez, José Manuel (2009)
This research work is orientated to analyze the technological innovations in the micro and small enterprises (MYPE) in the shoes sector. The implicit proposal is that the micro and small enterprises of this sector require to do technological innovations which make possible to achieve better levels of quality of their pro-ducts,and improve the competitiveness which let them to con-solidate the national market and to project themselves to the external market. All of these can produce a higher profitability because to achieve these objectives these enterprises should standardi- ze their products which need, necessarily, a technological inno- vation in management, processes and equipment.